Enhancing satisfaction and sustainable management: Whale watching in the Azores. (June 2016) - Bentz, Julia; Lopes, Fernando; Calado, Helena; Dearden, Philip
Abstract: This study explores satisfaction with whale watching tours in relationship to expectations and demographic variables and identifies tour aspects that contribute to satisfaction. Based on a survey of 466 participants it applies both importance-performance (IP) analysis and a performance-only perspective to strengthen the reliability of the results and enable a critical analysis of both approaches. Environmental friendly conditions were the most important expectation. Seeing one whale, seeing lots of whales, the cost of the trip and the boat type were the most influential factors contributing to satisfaction. Cost has not been previously identified as a factor influencing the satisfaction of whale watching customers. Satisfaction was related to participants' place of residence, with Northern Americans and Northern Europeans being more satisfied than participants from Southern and Western Europe. Some results of the IP analysis have little impact on satisfaction, suggesting that the performance-only approach provides a more valid insight into satisfaction. Highlights: Seeing whales, cost of the trip, boat type contribute to whale watching satisfaction. Satisfaction is related to participants' place of residence. Performance-only approach provides better insight to satisfaction than IP analysis.